إجراءات تأديب الموظف العمومي في التشريع الجزائري - لعجال خالد (المسيلة, 2023)
ان النظام التأديبي للموظف العام في الجزائر يعتبر جوهر توازن الجهاز اإلداري و استمرار المرافق العامة و تحسنها ، حيث انه يلعب دورا حيويا في النظام الوظيفي و يحظى بأهمية كبيرة و بالغة في الدولة . العتباره األداة الوحيدة لتوازن العالقة بين الموظف العام و الوظيفة العامة في حالة ارتكاب خطأ من طرف الموظف العام ، اذ انه يتدخل لمواساة العالقة بين الوظيفة و الموظف و ذلك حفاظا على كرامة الوظيفة و حماية الموظف و حسن سير المرافق العامة . لذلك فقد حرص المشرع الجزائري على إيجاد نظام تأديبي فعال للحد من ارتكاب األخطاء و الجرائم التأديبية ، و ذلك من خالل االمر 03-06 القانون األساسي للوظيفة العامة الذي أتى ليبين الحقوق و الواجبات للموظف العام و النظام التأديبي في حال حاول الموظف و كافة اإلجراءات المتبعة ضد الموظف و تصنيفات العقوبات حسب خطورة و جسامة الفعل المرتكب . 66 Summary : The disciplinary system for public employees in Algeria is considered as an essential core which maintains balance within the administrative apparatus with regard to its continuity and improvement of public facilities. This system plays a major role in the employment system as it holds great importance in the state. It is regarded as the sole tool for maintaining the balance between the public employee and the public function in case an error is being committed by the public employee. In fact, the disciplinary system for public employees intervenes to reconcile the relationship between the function and the employee, thereby preserving the dignity of the position, protecting the employee, and ensuring the smooth operation of public facilities. Therefore, the Algerian legislator has always been keen to establish an effective disciplinary system to reduce the occurrence of errors and disciplinary offenses. This was achieved through Law No. 06-03, the fundamental law of public employment, which clarifies the rights and duties of public employees, as well as the disciplinary system in case an employee attempts to commit misconduct. It also outlines the procedures followed against the employee and classifies the penalties according to the severity and seriousness of the committed act
Keywords: الاجراءات الادارية - تأديب الموظف العمومي - التشريع الجزائري